The Influence of Leadership and Work Motivation on Employee Performance at the Urban Village Office of Solok City - Husain, Faiz Muhammad; Yeni, Afni; Sriyanti, Esi (The Future of Education Journal, 2026)
This study aims to determine the influence of Leadership and Work Motivation on Employee Performance at the Lurah Office in Solok City. A quantitative method was employed, involving a sample of 106 respondents. The results of the statistical analysis indicate that Leadership partially has no significant effect on Employee Performance, as evidenced by the t-test value (tcount 1,565 < ttable 1,983) with a significance value of 0.121 > 0.05. Conversely, Work Motivation partially has a significant effect on Employee Performance, as demonstrated by the t-test value (tcount 6,561 > ttable 1,983) and a significance value of 0.000 < 0.05. Furthermore, the study concludes that Leadership and Work Motivation simultaneously influence Employee Performance at the Lurah Office in Solok City. This is supported by the F-test results (fcount 55,941 > ftable 3,058) with a significance level of 0.000, which is considerably lower than alpha (0.05). The R-Square value was found to be 0.521, indicating that these variables contribute 52.1% to Employee Performance, while the remaining 47.9% is influenced by other variables not included in this study.